Oral corrective feedback on L2 writing: Two approaches compared - Erlam, R.; Ellis, Rod; Batstone, R. (2013)
Corrective feedback (CF) research conducted within a cognitive-interactionist framework has examined the effectiveness of specific types of CF (e.g. Ellis etal., 2006). In contrast, CF research conducted within a sociocultural framework has sought to show how tailoring the feedback to the learners' zone of proximal development assists learning (e.g. Aljaafreh and Lantolf, 1994). The study reported in this article was designed to compare these two approaches to investigating CF by examining two types of feedback on students' errors in oral conferences following two pieces of writing. Some students received 'graduated feedback' in accordance with sociocultural theory and others explicit feedback in accordance with cognitive-interactionist theory. The detailed analysis of the feedback sessions showed that while the graduated feedback was effective in promoting self-correction, there was no evidence of any systematic reduction in the level of assistance provided over time. In contrast, the explicit feedback resulted in less self-correction but was accomplished much more quickly. © 2013 .